Genome‐Wide Association Study of 13 Traits in Maize Seedlings under Low Phosphorus Stress. Issue 3 (1st November 2019) - Wang, Qing‐Jun; Yuan, Yibing; Liao, Zhengqiao; Jiang, Yi; Wang, Qi; Zhang, Litian; Gao, Shibin; Wu, Fengkai; Li, Menglu; Xie, Wubing; Liu, Tianhong; Xu, Jie; et al.
Abstract : Core Ideas: Low P stress is a global issue for grain production. Significant phenotypic differences were detected among 13 traits in 356 maize lines under P‐sufficient and P‐deficient conditions. Significant single nucleotide polymorphisms (SNPs) and low‐P stress‐responsive genes were identified for 13 maize root traits based on a genome‐wide association study. Hap5, harboring 12 favorable SNPs, could enhance strong root systems and P absorption under low‐P stress. Phosphorus is an essential macronutrient required for normal plant growth and development. Determining the genetic basis of root traits will enhance our understanding of maize's ( Zea mays L.) tolerance to low‐P stress. Here, we identified significant phenotypic differences for 13 traits in maize seedlings subjected to P‐sufficient and P‐deficient conditions. Six extremely sensitive and seven low‐P stress tolerant inbreds were selected from 356 inbred lines of maize. No significant differences were observed between temperate and tropical–subtropical groups with respect to trait ratios associated with the adaptation to low‐P stress. The broad‐sense heritability of these traits ranged from relatively moderate (0.59) to high (0.90). Through genome‐wide association mapping with 541, 575 informative single nucleotide polymorphisms (SNPs), 551, 1140 and 1157 significant SNPs were detected for the 13 traits in 2012, 2016 and both years combined, respectively, along with 23 shared candidate genes, seven of which overlapped with reported quantitative trait loci and genes for low‐P stress. Five haplotypes located in candidate gene GRMZM2G009544 were identified; among these, Hap5, harboring 12 favorable SNP alleles, showed significantly greater values for the root traits studied than the other four haplotypes under both experimental conditions. The candidate genes and favorable haplotypes and alleles identified here provide promising resources for genetic studies and molecular breeding for improving tolerance to abiotic stress in maize.